Histidine-rich calcium binding protein: the new regulator of sarcoplasmic reticulum calcium cycling - Arvanitis, DA; Vafiadaki, E.; Sanoudou, D.; Kranias, EG (J Mol Cell CardiolJ Mol Cell CardiolJ Mol Cell Cardiol, 2011)
The histidine-rich calcium binding protein (HRC) is a novel regulator of sarcoplasmic reticulum (SR) Ca(2+)-uptake, storage and release. Residing in the SR lumen, HRC binds Ca(2+) with high capacity but low affinity. In vitro phosphorylation of HRC affects ryanodine affinity of the ryanodine receptor (RyR), suggesting a functional role of HRC on SR Ca(2+)-release. Indeed, acute HRC overexpression in isolated rodent cardiomyocytes decreases Ca(2+)-induced Ca(2+)-release, increases SR Ca(2+)-load, and impairs contractility. The HRC effects on RyR may be regulated by the Ca(2+)-sensitivity of its interaction with triadin. However, HRC also affects the SR Ca(2+)-ATPase, as shown by HRC overexpression in transgenic mouse hearts, which resulted in reduced SR Ca(2+)-uptake rates, cardiac remodeling and hypertrophy. In fact, in vitro generated evidence suggests that HRC directly interacts with SR Ca(2+)-ATPase2, supporting a dual role of HRC in Ca(2+)-homeostasis: regulation of both SR Ca(2+)-uptake and Ca(2+)-release. Furthermore, HRC plays an important role in myocyte differentiation and in antiapoptotic cardioprotection against ischemia/reperfusion induced cardiac injury. Interestingly, HRC has been linked with familiar cardiac conduction disease and an HRC polymorphism was shown to associate with malignant ventricular arrhythmias in the background of idiopathic dilated cardiomyopathy. This review summarizes studies, which have established the critical role of HRC in Ca(2+)-homeostasis, suggesting its importance in cardiac physiology and pathophysiology.
Arvanitis, Demetrios AVafiadaki, ElizabethSanoudou, DespinaKranias, Evangelia GengP50 HL077101-050003/HL/NHLBI NIH HHS/R01 HL026057-31/HL/NHLBI NIH HHS/R01 HL064018-12/HL/NHLBI NIH HHS/HL26057/HL/NHLBI NIH HHS/R37 HL026057/HL/NHLBI NIH HHS/HL77101/HL/NHLBI NIH HHS/R01 HL026057/HL/NHLBI NIH HHS/HL64018/HL/NHLBI NIH HHS/R01 HL064018/HL/NHLBI NIH HHS/P50 HL077101/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tReviewEngland2010/09/03 06:00J Mol Cell Cardiol. 2011 Jan;50(1):43-9. doi: 10.1016/j.yjmcc.2010.08.021. Epub 2010 Aug 31.
Keywords: Animals; Arrhythmias, Cardiac/metabolism; Calcium-Binding Proteins/*metabolism; Calcium/*metabolism; Humans; Proteins/*metabolism; Sarcoplasmic Reticulum/*metabolism